Design of Cost-Efficient QCA Reversible Circuits via Clock-Zone-Based Crossover - Sasamal T.N.; Singh A.K.; Mohan A. (My University, 2025)
Nanotechnologies, remarkably Quantum-dot Cellular Automata (QCA), offer an attractive perspective for future computing technologies. In this paper, QCA is investigated as an implementation method for reversible logic. A novel Reversible Gate is developed using QCA technology. Performance of the proposed gate is verified using thirteen standard three variables Boolean functions, which demonstrate from 14.3% to 42.8% superiority in term of gate counts obtained with other reversible gates. Proposed reversible gate requires switching and leakage energy dissipation of 0.168 eV and 0.271 eV, respectively, at 1.5 Ek energy level. The proposed gate uses 146 cells occupying only 0.14 μ m2 area and then used to design a full adder. We use a coplanar QCA crossover architecture in the designs that uses non-adjacent clock zones for the two crossing wires. These designs have been realized with QCADesigner. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.